Pengaruh Partisipasi Orang Tua dalam Proses Pembelajaran terhadap Prestasi Akademik Siswa Sekolah Dasar - Rizkia Nurul Wafa; Ibnu Muthi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to investigate the impact of parental involvement in the learning process on the academic performance of elementary school students. The active and supportive participation of parents in their children's education has been proven to have a significantly positive effect on students' academic achievement. Research findings indicate that parental engagement in teaching and learning activities, both at home and at school, not only enhances students' motivation to learn but also contributes to improved performance in cognitive, psychomotor, and affective aspects. This involvement encompasses open communication, emotional support, and adequate provision of learning resources. Furthermore, effective collaboration between parents and teachers strengthens students' commitment to learning and achieving better academic outcomes. Other factors influencing students' academic performance include individual interest, motivation, and talent. Therefore, optimizing the role of parents in the educational process is crucial for attaining optimal academic performance at the elementary school level.